Overexpression of EGFR and TGFα in von Hippel–Lindau-Related Central Nervous System Hemangioblastomas - Liu, Zhen; Li, Liang; Yi, Zhiqiang; Duan, Hongzhou; Lu, Runchun; Li, Chunwei; Zhou, Jingcheng; Gong, Kan (Frontiers in Oncology, 2020)
Background: Central nervous system (CNS) hemangioblastomas (HGBs) are the most frequent cause of mortality in patients with von Hippel–Lindau (VHL) disease. Characteristics of multiple and recurrent disease cause certain difficulties in the treatment of CNS HGBs. Methods: VHL-related HGB cases treated surgically at our hospital from September 2015 to February 2019 were analyzed. Patients meeting the clinical diagnostic criteria underwent genetic testing. Real-time PCR and immunohistochemistry were used in HGBs to verify differential expression of mRNAs and proteins, respectively. Furthermore, correlations between the differentially expressed proteins and the histological grading, genetic mutations, and tumor burden were also analyzed. Results: A total of 21 patients with VHL syndrome confirmed by genetic testing (missense group, 9; partial deletion group, 12) were enrolled, and 30 CNS HGBs from these patients were studied. Clinical data showed that men at first operation were significantly younger than females (p = 0.005). Real-time PCR demonstrated that EGFR (p = 0.017) and TGFα (p = 0.017) mRNA expression in VHL-related HGBs was significantly higher than that in the control group. Immunohistochemistry showed that the mean optical density in VHL-related HGBs was significantly higher than that in controls (EGFR, p = 0.007; TGFα, p = 0.021). Finally, the cyst volume was related to the upregulation of EGFR (r = 0.782, p < 0.01). Conclusion: Overexpression of EGFR and TGFα may contribute to tumor growth in VHL-related CNS HGBs. The cyst volume was associated with EGFR overexpression. These results provide information for the management of VHL-related HGBs in the era of targeted therapeutics.